An exploratory study of the dose correlation between point B and metastatic lymph nodes in three‐dimensional high‐dose‐rate brachytherapy for cervical cancer. Issue Volume 6:Issues 3(2022) (10th August 2022) - Yang, Dongming; Gao, Yuhua
Abstract: Objective: To determine the dose correlation between point B and metastatic lymph nodes in cervical cancer treated with three‐dimensional (3D) high‐dose‐rate (HDR) brachytherapy. Methods: A retrospective study was conducted involving 30 cervical cancer patients with lymph node metastases who completed 3D HDR brachytherapy at Liaoning Cancer Hospital and Institute from May 2019 to November 2020. Brachytherapy was performed with a Fletcher applicator at a prescribed dose of 28 Gy/4 f. Computed tomography images of the external irradiation target were fused with delineated images of the brachytherapy target on the MIM system. The minimum dose received by 90% of the volume (D90 ) was read on the MIM system for all metastatic lymph nodes and the point B dose was read for the brachytherapy target area. In total, 78 metastatic lymph nodes from 30 patients with cervical cancer were included in this study, including para‐aortic, common iliac, external iliac, internal iliac, obturator, and inguinal lymph nodes. Paired t ‐tests and Pearson correlation coefficient analyses were performed to examine the difference in the equivalent dose between each group of metastatic lymph nodes and point B. Results: The mean equivalent point B dose was 6.69 ± 1.08 Gy. There were significant differences in dose between point B and the para‐aortic, common iliac, external iliac, internal iliac, and inguinal lymph nodes ( p < 0.05), with a weak positive correlation ( r < 0.4). There was no statistically significant difference in dose between obturator lymph nodes and point B ( p = 0.3999), with a positive correlation ( r = 0.65). Conclusion: 3D HDR brachytherapy contributed significantly to pelvic lymph node doses in cervical cancer patients with lymph node metastasis, but less to para‐aortic and inguinal lymph node doses. The dose at point B grossly overestimated the mean dose to pelvic lymph nodes; only the dose to obturator lymph nodes was similar to that of point B, with a slightly positive correlation. Abstract : 3D high‐dose‐rate brachytherapy contributes significantly to pelvic lymph nodes in cervical cancer patients with lymph nodes metastases.